Fluid mechanics fundamentals and applications - Çengel, Yunus A.; Cimbala, John M. (McGraw Hill, 2014)
Covers the basic principles and equations of fluid mechanics in the context of numerous and diverse real-world engineering examples. This title helps students develop an intuitive understanding of fluid mechanics by emphasizing the physics, using figures, numerous photographs and visual aids to reinforce the physics